Evaluation of ruminal degradability and metabolism of feedlot finishing diets with or without cotton byproducts. (10th August 2020) - Warner, Andrea L; Beck, Paul A; Foote, Andrew P; Pierce, Kaitlyn N; Robison, Colton A; Stevens, Nicole E; Wilson, Blake K
Abstract: Cotton byproducts can be an economical source of protein, fat, and fiber in cattle finishing diets. The objectives of this study were 1) to assess the effects of including whole cottonseed (WCS ) and cotton gin trash (CGT ) in finishing diets on in situ ruminal degradability and 2) to determine the effects of including cotton byproducts in a finishing diet on rumen fluid pH, lactate, and volatile fatty acid concentrations. Six ruminally cannulated steers were used in a crossover design. Treatments included a control diet (CON ; 7% prairie hay [PH ], 15% Sweet Bran, 67.25% rolled corn, and 5% liquid supplement) and a cotton byproduct diet (CTN ; 7% CGT, 15% WCS, 72.25% rolled corn, and 5% water). Both diets included 0.75% urea and 5% dry supplement. In situ bags containing individual diet ingredients and whole diet samples were incubated in the rumen for up to 96 h. Rumen fluid samples were collected over a 24-h period. No treatment × substrate interactions were detected for any fraction of dry matter (DM ) or organic matter (OM ) degradability for individual ingredients or whole diets ( P ≥ 0.14). The A, B, and C fractions, disappearance rate (Kd), and effective degradability of DM and OM differed between diet ingredients ( P ≤ 0.04) but were not different between CON and CTN substrates ( P ≥ 0.25). A treatment × substrate interaction ( P = 0.04) was detected for the effective degradability of neutral detergent fiber (NDF ) of CGT and PH but there was no interaction for other fractions ( P ≥ 0.27). The A fraction of NDF was greater ( P < 0.001) for CGT than PH; however, the B fraction of NDF tended to be greater ( P = 0.08) for PH than CGT. No differences ( P ≥ 0.37) were detected for the % NDF disappearance at 48 h between CON and CTN substrates. A tendency for a treatment × substrate interaction ( P = 0.10) was observed for the effective degradability of starch among diets; however, when the CON substrate was incubated in steers consuming the CON diet, effective degradability of starch was not different ( P = 0.84) from when the CTN diet was incubated in steers consuming the CTN diet. There was no treatment × time interaction or treatment effect for rumen pH; however, there was a time effect ( P = 0.03). Steers consuming the CTN diet had greater molar proportions of acetate and decreased molar proportions of propionate compared with CON steers ( P < 0.01). This experiment suggests that there are minimal differences between the digestibility of finishing diets containing cotton byproducts and those comprised of traditional finishing diet ingredients.